TO STUDY THE EFFICACY OF NISHAKANAK KALKA LEPA IN STANPEEDA W.S.R. TO CYCLIC MASTALGIA (AYUSHDHARA, 2021)
Stanpeeda (Mastalgia) is a commonly occurred breast pain that a female suffers from during her lifetime. Approximately two-thirds of women develop this pain during their reproductive life and may seek medical attention when it adversely affects their daily life. The breast pain may vary from mild to severe, could be intermittent or constant. According to Ayurveda, Stanpeeda can be correlated with Mastalgia. The objectives are to study of Stanpeeda with reference to cyclic mastalgia and to study the effect of Nisha kanak kalka lepa in Stanpeeda for 7 days, when cyclic mastalgia occurs. The study was conducted at Stree Rog prasuti tantra department, Hon. Shri. Annasaheb Dange Ayurved Medical College, Post Graduate & Research Center, Sangli, Maharashtra. Total number of 60 patients of 18-35 years age group having Stanapeeda were selected and treated with Nisha Kanak Kalka lepa. In this study the importance of Nisha (Rhizome of Haridra) and Kanak (Dhatura patra) and its possible action on each symptom was explained. Out of 60 patients studied, 21 patients (35%) showed marked improvement, 36 patients (60%) showed moderate improvement while 3 patients (5%) were mildly improved. Hence Nisha and Kanak Kalka lepa had significant result in Stana Peeda.